Adrenal Crisis Caused by Inhaled Fluticasone in an Adolescent with Cystic Fibrosis and Advanced Hepatopathy: A Case Report - C. Denne; A. E. Vogl-Voswinckel; A. Gruebl; S. Burdach (Case Reports in Pulmonology)
Inhaled corticosteroids are widely accepted in the treatment of cystic fibrosis. Long-term use may cause systemic complications, especially high-dose fluticasone. We report about a young man who presented with encephalopathy after excessive physical activity caused by secondary adrenal insufficiency. He recovered quickly after systemic corticosteroid replacement therapy. This problem is considered to be underdiagnosed in clinical practice.